Quantifying interactions in the water-energy-food nexus: data-driven analysis utilizing a causal inference method - Saed, Behdad; Elshorbagy, Amin; Razavi, Saman (Frontiers in Environmental Science, 2024)
There is a pressing need for a holistic approach to optimize water-energy-food (WEF) resources management and address their interlinkages with other resources due to population growth, socio-economic development, and climate change. However, the structural and spatial extent of the WEF system boundaries cause exponential growth in computational complexity, making exploratory data analysis crucial to obtain insight into the system's characteristics and focus on critical components. This study conducts a multiscale investigation of the WEF nexus within the Canadian prairie provinces (Alberta, Saskatchewan, and Manitoba), utilizing causal-correlational analysis and the Multispatial Convergence Cross Mapping (mCCM) method. Initially, we employed regression analysis to establish fitted equations, along with their coefficients of determination (R²), to identify patterns among pairs of WEF sectors, GDP, and GHG emissions. Subsequently, we conducted a causal analysis between these correlated pairs using mCCM method. Moreover, we explored the cause-and-effect relationships between these sector pairs within the Canadian prairie provinces both individually and as a single unit over the period 1990-2020. Results show that energy and water are the most influential sectors on greenhouse gas (GHG) emissions and gross domestic product (GDP) in the prairies as a whole. Energy has a stronger influence on GHG compared to water and food sectors, while water has the strongest causal influence on the GDP of Alberta, and food and energy do so for Saskatchewan and Manitoba, respectively. The trade-offs for improving WEF nexus security strongly depend on the scale of the system under investigation, highlighting the need for careful deliberations around boundary judgment for decision-making. This study provides a better understanding of the WEF-GDP-GHG nexus in the Canadian prairies and existing interrelationships among the aforementioned sectors, helping to build more efficient WEF nexus models for further simulation and scenario analysis.